Environmentally relevant concentrations of a common insecticide increase predation risk in a freshwater gastropod - Salice, Christopher J (Ecotoxicology (London, England), 2013)
Ecological receptors are faced with a multitude of stressors that include abiotic and biotic factors creating a challenge for assessing risk of chemical exposure. Of particular interest and importance are the effects of contaminants on inter-species interactions such as competition and predator-prey relationships. The objective of this study was to determine whether environmentally relevant concentrations of the commonly used insecticide, malathion, would alter predator avoidance behavior in a freshwater gastropod that could translate to increased predation risk. We exposed adult Physa pomilia snails to 0, 0.25, or 1.0 mg/L malathion for 2, 24, or 48 h and evaluated predator avoidance using a behavioral assay in which snails were exposed to cues from predatory crayfish. We found a significant reduction in predator avoidance in snails exposed to both concentrations of malathion after 48 h of exposure. To evaluate whether observed effects of malathion on predator avoidance actually increased susceptibility of snails to predators, we conducted a predator challenge experiment. Snails exposed to 0.25 mg/L malathion for 48 h were significantly more susceptible to predation. That increased predation risk was evident 48 h after initial malathion exposures is a unique result because most studies have evaluated behavioral responses soon after (<12 h) initiation of pesticide exposure. The extent to which the observed interactions affect natural populations, and the mechanisms through which they are mediated are largely unexplored. However, our study is the first to show that a commonly used insecticide decreases predator avoidance and may actually increase predation susceptibility in gastropods at concentrations several orders of magnitude below acute toxicity levels